Crohn's and Colitis Canada's 2021 Impact of COVID-19 & Inflammatory Bowel Disease in Canada: A Knowledge Translation Strategy. (5th November 2021) - Kaplan, Gilaad G; Windsor, Joseph W; Crain, Janet; Barrett, Lisa; Bernstein, Charles N; Bitton, Alain; Chauhan, Usha; Coward, Stephanie; Fowler, Sharyle; Ghia, Jean-Eric; Gibson, Deanna L; Griffiths, Anne M; et al.
Abstract: The prevalence of inflammatory bowel diseases (IBD), Crohn's disease and ulcerative colitis, in Canada, is over 0.75% in 2021. Many individuals with IBD are immunocompromised. Consequently, the World Health Organization's declaration of a global pandemic uniquely impacted those with IBD. Crohn's and Colitis Canada (CCC) formed the COVID-19 and IBD Taskforce to provide evidence-based guidance during the pandemic to individuals with IBD and their families. The Taskforce met regularly through the course of the pandemic, synthesizing available information on the impact of COVID-19 on IBD. At first, the information was extrapolated from expert consensus guidelines, but eventually, recommendations were adapted for an international registry of worldwide cases of COVID-19 in people with IBD. The task force launched a knowledge translation initiative consisting of a webinar series and online resources to communicate information directly to the IBD community. Taskforce recommendations were posted to CCC's website and included guidance such as risk stratification, management of immunosuppressant medications, physical distancing, and mental health. A weekly webinar series communicated critical information directly to the IBD community. During the pandemic, traffic to CCC's website increased with 484, 755 unique views of the COVID-19 webpages and 126, 187 views of the 23 webinars, including their video clips. CCC's COVID-19 and IBD Taskforce provided critical guidance to the IBD community as the pandemic emerged, the nation underwent a lockdown, the economy reopened, and the second wave ensued. By integrating public health guidance through the unique prism of a vulnerable population, CCC's knowledge translation platform informed and protected the IBD community.